2017
DOI: 10.1103/physreve.96.022219
|View full text |Cite
|
Sign up to set email alerts
|

Nonconservative higher-order hydrodynamic modulation instability

Abstract: The modulation instability (MI) is a universal mechanism that is responsible for the disintegration of weakly nonlinear narrow-banded wave fields and the emergence of localized extreme events in dispersive media. The instability dynamics is naturally triggered, when unstable energy side-bands located around the main energy peak are excited and then follow an exponential growth law. As a consequence of four wave mixing effect, these primary side-bands generate an infinite number of additional side-bands, formin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…[80] and [83]. Such observations are also known to be related to the phenomenon of higher modulation instability recently observed in optics and in hydrodynamics [82,[84][85][86], wherein non-ideal excitation of first-order breathers (ABs, PS...) or propagation losses were identified as perturbations that introduce deviations from the expected nonlinear dynamics on longer propagation distances (simply due the unstable nature of NLS breathers). In particular, it was shown that higher order modulation instability arises from perturbations on breathers close to the PS limit, thus resulting in a nonlinear superposition (i.e., complex arrangement) of several elementary breathers.…”
Section: Nonlinear Spectral Analysis Of the Peregrine Soliton Obmentioning
confidence: 85%
“…[80] and [83]. Such observations are also known to be related to the phenomenon of higher modulation instability recently observed in optics and in hydrodynamics [82,[84][85][86], wherein non-ideal excitation of first-order breathers (ABs, PS...) or propagation losses were identified as perturbations that introduce deviations from the expected nonlinear dynamics on longer propagation distances (simply due the unstable nature of NLS breathers). In particular, it was shown that higher order modulation instability arises from perturbations on breathers close to the PS limit, thus resulting in a nonlinear superposition (i.e., complex arrangement) of several elementary breathers.…”
Section: Nonlinear Spectral Analysis Of the Peregrine Soliton Obmentioning
confidence: 85%
“…Carter & Govan [4] showed that the vDysthe equation accurately models data from experiments in which frequency downshift was observed and experiments in which frequency downshift was not observed. Kimmoun et al [14] showed that the vDysthe equation accurately models data from experiments conducted in a much larger experimental tank. When δ = ǫ = 0, the viscous Dysthe equation reduces to the NLS equation,…”
Section: Asymptotic Modelsmentioning
confidence: 99%
“…However, Segur et al [22] noted that in their experiments, the FD in the spectral peak sense was always accompanied by a decrease in P. Thus, our conclusions for FD in the spectral peak sense are based on the evolution of P. These conclusions are consistent with our numerical results that are discussed in Section 5. We also note that in experiments, there is damping, which causes a nearly exponential decay of both M and P. Thus, we seek a model that predicts both this decay as well as the FD exhibited by an evolving P. The vDysthe equation, (8), the IS equation, (14), and the dGT equation, (15), have all of these ingredients. The vDysthe equation does not preserve M, P, or ω m in χ (dimensionless distance down the tank).…”
Section: Predicted Evolution Of ω M M and Pmentioning
confidence: 99%
“…Furthermore, these results can be considered to be analogous to the observations of MI and the Fermi-Pasta-Ulam recurrence, starting from three wave systems, as reported in Tulin and Waseda (1999). More details can be found in Erkintalo et al (2011, Chabchoub and Grimshaw (2016), Kimmoun et al (2016Kimmoun et al ( , 2017.…”
Section: Numerical Simulations and Experimental Set-upmentioning
confidence: 57%